Mind and Consciousness in Indian Philosophy. - Lysenko, Victoria G. (Russian Studies in Philosophy, 2018)
How is the approach of Indian philosophers to the study of consciousness different from that of their Western counterparts? To answer this question, it is necessary to understand how the Indian philosophical tradition distinguishes between consciousness and non-consciousness. How does it present and solve the mind-body problem? The article explores the difference in understanding of mind and consciousness in some schools of Indian philosophy. First, the article considers some major Indian philosophical principles underlying the relationship between mind and consciousness which make the Indian tradition unique in comparison to the West. The last part of the article analyzes one by one the most representative Indian philosophical theories of mind and consciousness (with their corresponding terminology).